2016
DOI: 10.24198/jsk.v1i3.10358
|View full text |Cite
|
Sign up to set email alerts
|

Skrining Thalassemia Beta Minor Pada Siswa Sma Di Jatinangor

Abstract: Jenis Thalassemia yang paling banyak ditemukan adalah Thalassemia beta. Tercatat 10% penduduk Indonesia merupakan pembawa gen Thalassemia beta. Thalassemia beta minor sulit dideteksi karena bersifat asimtomatik sehingga peranan skrining sebagai deteksi dini sangat diperlukan. Sampai dengan saat ini di Indonesia belum dilakukan program skrining rutin Thalassemia.Tujuan penelitian ini untuk mengetahui frekuensi Thalassemia beta minor pada siswa- siswi SMA di Jatinangor. Metode Penelitan deskriptif kuantitatif, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…A thalassemia minor screening in Jatinangor, stated that 9.3% of all high school student respondents who are willing to participate in screening, are suspected with thalassemia beta minor. 3 Data from Thalassemia Foundation and Association of Thalassemia Parents of Indonesia showed that there were 669 people (5.8%) of the 12,038 general public examined through thalassemia screening from 2008-2017 who are carriers of the thalassemia gene. 4 Data from RSUD dr. Soedarso Pontianak, a referral hospital in West Kalimantan Province, showed 1429 visits of thalassemia patients as outpatients throughout 2018.…”
Section: Introductionmentioning
confidence: 99%
“…A thalassemia minor screening in Jatinangor, stated that 9.3% of all high school student respondents who are willing to participate in screening, are suspected with thalassemia beta minor. 3 Data from Thalassemia Foundation and Association of Thalassemia Parents of Indonesia showed that there were 669 people (5.8%) of the 12,038 general public examined through thalassemia screening from 2008-2017 who are carriers of the thalassemia gene. 4 Data from RSUD dr. Soedarso Pontianak, a referral hospital in West Kalimantan Province, showed 1429 visits of thalassemia patients as outpatients throughout 2018.…”
Section: Introductionmentioning
confidence: 99%
“…A question that measures the proportion of respondents who have had screening before is also included. The decision to include these questions is influenced by previous studies that suggested there is a high prevalence of thalassemia carriers across several areas in Indonesia [46][47][48][49][50]. It is important to understand the trend of the answers to these questions in order to inform future thalassemia prevention, screening, and education programs in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis technique used in this study is the Mediation Model Linear Regression analysis technique (Path Analysis) to look for the influence of the independent variable (X) with the dependent variable (Y) with the mediation variable (Z). Before the hypothesis test is carried out, classical assumptions will be tested which include; normality test and linearity test (Ghozali & Dalimoenthe, 2016).…”
Section: F Data Analysis Techniquesmentioning
confidence: 99%